(Glyco)sphingolipids Are Sorted in Sub-Apical Compartments in HepG2 Cells: A Role for Non-Golgi–Related Intracellular Sites in the Polarized Distribution of (Glyco)sphingolipids - van IJzendoorn, Sven C.D. (The Rockefeller University Press, 1998)
In polarized HepG2 cells, the fluorescent sphingolipid analogues of glucosylceramide (C(6)-NBD-GlcCer) and sphingomyelin (C(6)-NBD-SM) display a preferential localization at the apical and basolateral domain, respectively, which is expressed during apical to basolateral transcytosis of the lipids (van IJzendoorn, S.C.D., M.M.P. Zegers, J.W. Kok, and D. Hoekstra. 1997. J. Cell Biol. 137:347–457). In the present study we have identified a non-Golgi–related, sub-apical compartment (SAC), in which sorting of the lipids occurs. Thus, in the apical to basolateral transcytotic pathway both C(6)-NBD-GlcCer and C(6)-NBD-SM accumulate in SAC at 18°C. At this temperature, transcytosing IgA also accumulates, and colocalizes with the lipids. Upon rewarming the cells to 37°C, the lipids are transported from the SAC to their preferred membrane domain. Kinetic evidence is presented that shows in a direct manner that after leaving SAC, sphingomyelin disappears from the apical region of the cell, whereas GlcCer is transferred to the apical, bile canalicular membrane. The sorting event is very specific, as the GlcCer epimer C(6)-NBD-galactosylceramide, like C(6)-NBD-SM, is sorted in the SAC and directed to the basolateral surface. It is demonstrated that transport of the lipids to and from SAC is accomplished by a vesicular mechanism, and is in part microtubule dependent. Furthermore, the SAC in HepG2 bear analogy to the apical recycling compartments, previously described in MDCK cells. However, in contrast to the latter, the structural integrity of SAC does not depend on an intact microtubule system. Taken together, we have identified a non-Golgi–related compartment, acting as a “traffic center” in apical to basolateral trafficking and vice versa, and directing the polarized distribution of sphingolipids in hepatic cells.